Multiple cytokine responses in discriminating between active tuberculosis and latent tuberculosis infection. (January 2017) - Wu, Jing; Wang, Sen; Lu, Chanyi; Shao, Lingyun; Gao, Yan; Zhou, Zumo; Huang, Heqing; Zhang, Ying; Zhang, Wenhong
Summary: Background: Cytokines play an important role in cell-mediated immune responses against Mycobacterium tuberculosis ( Mtb ) infection. Cytokine profile specifically associated with active tuberculosis (ATB) patients, subjects with latent tuberculosis infection (LTBI) and non-infected individuals remains to be determined. Methods: We enrolled a total of 92 subjects including patients with ATB ( n = 25), LTBI ( n = 36) and healthy controls (HC, n = 31) to investigate the cytokine production by peripheral blood mononuclear cells after Mtb purified protein derivative (PPD) stimulation which was evaluated by a beads-based multiplex assay system. Results: The production of IL-1β, IL-2, IL-6, IL-10, IL-17, G-CSF, IFN-γ, IP-10, MIP-1α and TNF-α was abundantly induced by PPD in all three groups. The levels of IL-2, IL-10, IFN-γ, IP-10 and TNF-α were significantly higher in LTBI group than in ATB group. The combination of PPD-stimulated IL-2 and IL-10 accurately identified 84.0% of ATB and 88.9% of LTBI. We validated the use of PPD-stimulated IL-2 and IL-10 test combined with T-SPOT. TB test in a cohort of 44 subjects with TB suspicion. The sensitivity and specificity of the combined test were 83.3% and 92.3%, respectively. The PPD-stimulated IL-2/IFN-γ ratio ( p < 0.001) in LTBI subjects was significantly higher than in active TB patients. Conclusion: Our study identified cytokine patterns characteristic of ATB and LTBI. Cytokines such as IL-2 and IL-10 may serve as biomarkers for distinguishing ATB from LTBI and healthy control and may contribute to intervention and improvement in TB diagnosis.